Management of online platform development and support process - Kateryna V. Vlasenko; Sergii V. Volkov; Iryna V. Lovianova; Olena O. Chumak; Irina V. Sitak; Dmytro Ye. Bobyliev (Academy of Cognitive and Natural Sciences, 2021)
The matter of building an optimal model of managing the online platform "Higher School Mathematics Teacher" is considered in this article. The existing researches on the management of online platform development and support process have been analyzed in this paper. The model developers described the process of building an online platform according to the Software Development Lifecycle rules. The researchers described an online course platform creation and functioning process that corresponds to a five-stage pedagogical ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) of online course preparation. The research describes the roles and objectives of online platform team members. These results allowed the authors of the article to model the organizational structure of online platform management. The method of survey among the team members of the online platform "Higher School Mathematics Teacher" and its participants was used to prove the efficiency of the offered model. The results allowed us to confirm the actuality of the research in the management of educational platforms, the convenience of teamwork in online platform management, and successful model implementation.